Integrasi Ijtihad dan Taqlid dalam Pengembangan Hukum Islam Kontemporer - Aji, Ahmad Mukri (BULETIN ADALAH, 2025)
This study examines the integration of ijtihad and taqlid in the development of contemporary Islamic law through a comparative ushul al-fiqh perspective. It argues that viewing these concepts dichotomously obscures their complementary epistemological roles. While ijtihad provides legal dynamism and adaptability, taqlid ensures continuity, stability, and legitimate transmission of scholarly authority. Through historical and methodological analysis, the study highlights taqlid metodologis and collective ijtihad as effective models for contextualizing Islamic law without undermining its classical foundations. This integrative approach enables Islamic legal reasoning to remain coherent, responsive, and normatively grounded amid modern social and intellectual transformations. Keywords: Ijtihad, Taqlid, Ushul al-Fiqh